PENGARUH BRAND AMBASSADOR, KUALITAS PRODUK DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK AVOSKIN DI KOTA BATAM - Sinaga, Sri Novianti; Purba, Tiurniari (SCIENTIA JOURNAL, 2025)
This research aims to examine the influence of brand ambassadors, product quality and e-WOM on purchasing decisions of Avoskin products in Batam City. This study uses a quantitative research method. The research sample consisted of 100 respondents who were people who had purchased and used Avoskin products in the Sagulung District, Batam City. The data collection method used was primary data. Data processing used the SPSS Version 26 program. Based on the data and analysis that have been carried out, this study shows that brand ambassadors positively and significantly influence purchasing decisions of Avoskin products in Batam City. In addition, product quality positively and significantly influences purchasing decisions of Avoskin products in Batam City. In e-WOM, it positively and significantly influences purchasing decisions of Avoskin products in Batam City. And simultaneously, brand ambassadors, product quality and e-WOM positively and significantly influence purchasing decisions of Avoskin products in Batam City